ANALYSIS OF THE SKILLS GAP IN TOURISM AND HOSPITALITY INDUSTRY IN KENYA - Francis Kabii; Ann Wamathai; John K. M.; Naghea Jilo (Centre For Tourism Planning and Development, 2019)
Most training institutions in Kenya have supply led training instead of demand-driven training thereby creating a supply of graduates whose knowledge and skills in not needed in the industry thereby creating a training gap between the educators and the industry. This paper aims to analyze the skills gap in the tourism and hospitality industry in Kenya. The objectives were to investigate the skills gap between tourism and hospitality graduates and industry expectations, examine the stakeholder's opinion on performance university graduates as compared to graduates from Technical and Vocational Education Training institutes and examine the emerging trends in human labour in tourism and hospitality that educators should anticipate. The sample size was 200 respondents composed of managers and supervisors from 2 stars to 5 stars rating hotels. Data was collected using questionnaires and interviews. It was found that the training institution applies supply-driven training instead of demand-driven thereby creating a shortage of adequately trained and skilled staff suitable for the tourism job market. The study recommends the involvement of educators and industry practitioners in the training resource persons and enforcement of the National Qualification Framework to ensure standardized curriculum contents in training institutions.